1981
DOI: 10.1002/art.1780241203
|View full text |Cite
|
Sign up to set email alerts
|

HLA—Bw35 and Prognosis in Adult Still's Disease

Abstract: Twenty-five patients with adult Still's disease were studied to determine clinical course and possible HLA associations. Two types of disease evolution were distinguishable clinically: a self-limited remitting disease with or without recurrent cyclic exacerbations was found in 11 patients, and a persistent disease with continuous activity for more than 1 year, generally accompanied by progressive joint disease, was determined in 8. Disease course could not be classified in 6 patients. The antigen frequencies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
3

Year Published

1985
1985
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 16 publications
0
22
1
3
Order By: Relevance
“…The nearly complete absence of Bw35 in the present series, which is probably due to a linkage disequilibrium of Bw35 with DR1, contrasts strongly with the results of Glass and Litrin (5) and Terkeltaub (9), who reported a significantly increased incidence of Bw35 in juvenile-and adult-onset Still's disease patients, respectively. In addition, since none of our 16 patients with self-limited disease, defined in the same way as Terkeltaub did (9), was positive for Bw35, we cannot support Terkeltaub's suggestion that Bw35 may be a favorable prognostic marker in AOSD.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…The nearly complete absence of Bw35 in the present series, which is probably due to a linkage disequilibrium of Bw35 with DR1, contrasts strongly with the results of Glass and Litrin (5) and Terkeltaub (9), who reported a significantly increased incidence of Bw35 in juvenile-and adult-onset Still's disease patients, respectively. In addition, since none of our 16 patients with self-limited disease, defined in the same way as Terkeltaub did (9), was positive for Bw35, we cannot support Terkeltaub's suggestion that Bw35 may be a favorable prognostic marker in AOSD.…”
Section: Discussioncontrasting
confidence: 81%
“…Previous HLA studies in juvenile patients with Still's disease have shown increased frequencies of B8 (3, Bw35 (5,6), Bw44 (6), DR4 (6), DR5 (7), and Dw7 (8). In adult patients, B14 (6), Bw35 (9), Cw4 (9), and DR7 (6) were reported to be increased (Table 3).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Consistent with this classification, strong associations with MHC class II are lacking in AOSD, although in some populations association with HLA-DR4, HLA-Bw35, or HLA-DRB1 have been occasionally observed [26,27]. Polymorphisms have been described in genes encoding innate immunity-associated factors and cytokines, such as IL-6, IL-1a, IL1-RN, macrophage inhibitory factor (MIF), or TNF in patients with sJIA [28][29][30] and IL-18, or MIF in patients with AOSD [31,32].…”
Section: Geneticsmentioning
confidence: 57%
“…HLA-DRB1*04 may be protective of the disease, whilst HLA-Bw35 conferred a better prognosis 6 . HLA-DRB1*14 alleles were more common in patients with the monocyclic systemic type of AOSD 7 , whilst chronic articular form of the disease was associated with HLA-DR2, DR5 and DQ1 alleles 8 .…”
Section: Epidemiologymentioning
confidence: 99%